Is There a General History? - Havelka, Miloš (Dějiny – teorie – kritika, 2019)
In connection with Horský’s contribution ‘“General History”, “Content-Oriented Philosophy” of History, and the Theory of Evolution’, Havelka considers the origins and content of general history and highlights the vagueness which characterised them in Czech historiographic discourse ever since the 1950s. He stresses differences between the terms ‘general history’ and ‘world history’ or rather our understanding of the ways in which one can or should progress from the factuality of particular historical events and their unrepeatable uniqueness in different places to their ‘general’ aspects and ‘unifying’ characteristics. In conjunction with this investigation, Havelka searches for the historical origins of use of the term ‘general history’ since the eighteenth century and traces the genesis of views which viewed the philosophy of history as the main route to knowledge of historical necessity. He contrasts these conceptions with the theoretically clearer and methodologically more sophisticated notion of ‘shared history’, which focuses on search for parallels and structural analogies between certain social, political, and civilisation processes that go beyond the schematic differences between national histories. Especially in the form of ‘comparative history’, its intentions and conclusions then also lead to a degree of generalising assessment.